The Shape of the Davidic Hope across the Book of the Twelve - Petterson, Anthony R. (2010)
It has recently been argued that the Book of the Twelve reflects a variety of views concerning the restoration of the Davidic monarchy, including optimism in the early Persian period and later criticism. The interpretation of Zechariah 11 and the texts concerning Zerubbabel is critical in this. This article presents an interpretation of these texts which coheres with Zechariah and the Book of the Twelve. The shape of the Davidic hope across the Book of the Twelve is then traced and it is observed that the hope for a future king from the house of David occurs at key points. This suggests that those who collected the Twelve sought to preserve the earlier prophetic hope for a future Davidic king.
Keywords: Zerubbabel; Zechariah; Twelve; Shepherd; Kingship; Haggai; Davidic; Coherence; Branch/Shoot